Effect of titanium segregation on interfacial misfit dislocation network in ni-based superalloys using molecular dynamics simulation [electronic resource] - Hasvadilla Roslan, 1991-, author 635318; Joy Rizki Pangestu Djuansjah, supervisor 549436; Fakulti Kejuruteraan Mekanikal 8081
Project Paper (Sarjana Muda Kejuruteraan (Mekanikal - Bahan)) - Universiti Teknologi Malaysia, 2014